Hepatic stereological analysis in obese Zucker rats (Leprfa) with dyslipidemia - Silvio Pires Gomes; Gabriela Salim de Castro; Vinicius Pedro Silva de Oliveira; Bruno Cogliati; Andressa Galvão da Silva Iacopino; Ivanir Santana de Oliveira Pires; Bruno Cesar Schimming; Fernanda Gosuen Gonçalves Dias; José Roberto Kfoury Junior; Tais Harumi de Castro Sasahara (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To characterize histologically and stereologically the hepatic steatosis in obese Zucker (fat, n = 6, with a mutation in the leptin receptor – Leprfa) and control Zucker (lean, n = 6) rats, analyzing macroscopic and microscopic differences to understand the influence of obesity on hepatic pathology. Methods: Zucker rats were fed standard chow for 90 days. Macroscopic, qualitative, and histoquantitative (stereological) approaches were used, involving body and liver weight measurement, morphological analysis, and histopathological classification of metabolic dysfunction-associated steatotic liver disease. Results: Zucker fat rats had higher body weight (p = 0.0022), liver weight (p = 0.0022), serum total cholesterol (p = 0.0022), and triacylglycerol (p = 0.0022) compared to Zucker lean rats. Stereological analysis showed that hepatocyte volume density (p = 0.0022) and total hepatocyte volume (p = 0.0001) were lower, and the volume density (p = 0.002) and total volume of steatosis (p = 0.002) were higher in Zucker fat rats compared to lean rats. Conclusion: The findings indicated that obesity induces significant alterations in the hepatic morphology of Zucker rats, showing that hepatocyte volume is lower in obese animals. This study reinforces the utility of the obese Zucker rat model to investigate the effects of obesity on liver health and suggests hepatic steatosis requires therapeutic strategies focused on modulating these parameters.